Intercomparison of radar meteor velocity corrections using different ionization coefficients - Williams, E. R. (2017)
Sensitive long‐wavelength radar observations of absolute velocity never previously published from Jicamarca are brought to bear on the long‐standing problem of radar detection of slow‐moving meteors. Attention is devoted to evaluating the ionization coefficient β(V) in the critically important velocity range of 11–20 km/s in recent laboratory measurements of Thomas et al. (2016). Theoretical predictions for β(V) based on the laboratory data, on Jones (1997), on Janches et al. (2014), and on Verniani and Hawkins (1964) are used to correct the incoming meteor velocities measured with the sensitive Jicamarca high‐power, large‐aperture radar operating at 6 m wavelength. All corrected distributions are consistent with the predictions of the Nesvorný model in showing pronounced monotonic increases down to the escape velocity (11 km/s). Such distributions may be essential to explaining the pronounced ledge in nighttime electron density and the rapid disappearance of electrons in meteor trails in the altitude range of 80–85 km.